Edukasi Pemanfaatan Jahe untuk Mengatasi Mual pada Kehamilan Trimester I di Puskesmas Putri Ayu - Fatihatul Hayati; Sri Maharani (3031-8572, 2022)
Nausea is one of the earliest, most common and most stressful symptoms associated with pregnancy. Most pregnant women experience nausea and even vomiting in the first trimester. Nausea in early pregnancy is often considered a common complaint experienced by pregnant women, so it is often ignored, but can cause discomfort and interfere with activities. Often pregnant women ask for both pharmacological and non-pharmacological therapy to overcome or reduce this discomfort. Initial management of nausea in the first trimester of pregnancy should be conservative with changes in diet, emotional support, and alternative therapies such as herbs. Traditional herbal ingredients that can be used include ginger, where ginger contains essential oils that have a refreshing effect and block the gag reflex, while gingerol can make blood and nerves work properly. For this reason, pregnant women need to be educated about the use of ginger to relieve nausea in the first trimester of pregnancy. This community service is carried out by providing health education through counseling to pregnant women about the use of ginger to treat nausea and vomiting in the first trimester of pregnancy, in mother class activities held at the Puskesmas Putri Ayu, Jambi City. The results of this activity were an increase in pregnant women's knowledge about how to deal with nausea by using ginger as an herbal therapy